The analysis of the phenomenon of reflexivity in psychotherapy supervision: A systematic literature review - Vaštakė, Marija; Skruibis, Paulius (Psichologija, 2021)
Reflexivity is a concept that is increasingly gaining prevalence in the literature of professional practice and it has been defined in a variety of ways; however, the differences in definition largerly depend on the context. Therefore, reflexivity development is the main goal of supervision; it is a powerful instrument that can impede the psychotherapist’s connection with his client, but there is no answer on what specifically enhances or decreases reflexivity during the supervision process. In the scientific articles analyzing supervision, there is no clear definition of the phenomenon of reflexivity and there is also a lack of empirical studies of reflexivity in supervision. The aim of this paper is to present our own definition and theoretical model of reflexivity in the psychotherapy supervision process as well as distinguish reflexivity between adjacent concepts like “reflection,” “self-reflection,” and “self-reflexivity.” We carried out a systematic review of literature within three databases and created a theoretical model of reflexivity in psychotherapy supervision. We also discuss the guidelines and methods for further empirical investigations of this phenomenon in psychotherapy supervision.
Keywords: reflexivity; psychotherapy supervision; supervision